PERCEPTUALS LEARNING STYLES PREFERENCES OF INTERNATIONAL MASTER'S STUDENTS IN MALAYSIA - Achmad Yudi Wahyudin; Akhyar Rido (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2020)
It has been a consensus that learning styles have been a predominant factor of success in master's degree program. Since the preferences of learning styles are affected by students' cultural background, this study was carried out to explore the perceptual learning style preferences of international Master’s students in a Malaysian university. Sixty students consisting of Indonesian, Iranian, and Libyan were involved in the present study. The findings reveal that Indonesian and Libyan students tended to be more kinesthetic/tactile learners while Iranian tended to be more visual learners. This study suggested practitioners use various learning strategies to cater the learning style preferences of the students.